Modernization and development as a motor of polity and policing - Frois, Catarina; Machado, H. (The Sage Handbook of Global Policing, 2016)
In the discourse of politicians and security force officials around the world, technology is frequently advanced as a powerful and innovative tool in the prevention, dissuasion and general struggle against crime. In the production of policies around the safety of goods and persons – that are enforced at local, regional, national and international levels – the use of advanced technological systems cuts across all areas of police activity.